Analisis Potensi Sektor Ekonomi Kabupaten Gresik - Hani Ristanti; Sri Muljaningsih (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Regional economic development is one of the planning activities that will be carried out by local governments to improve the economy of an area. This can be done according to the sectoral potential in each region. This study aims to determine the growth of the basic or leading sectors. In addition, the second objective is to find out the speed of growth and growth potential by comparing the sector in Gresik Regency with the sector of the province of East Java. The analysis in this study is a quantitative descriptive study, using secondary data and time series from GRDP data in Gresik Regency and East Java Province in the 2016-2020 period. The analytical method used is Location Quotient (LQ) analysis and Shift Share analysis. The results of the average LQ research in Gresik Regency for the 2016-2020 period show that there are 4 basic / superior sectors in Gresik Regency, while the average shift share research results are growing fast and encouraging the growth of GRDP in East Java Province 2016-2020 in the Regency while in Gresik there are 7 sectors, the locational sector which has strong competitiveness in 2016-2020 in Gresik Regency as many as 14 sectors.